Peningkatan Prestasi Belajar IPA tentang Tata Surya melalui Penerapan Model Pembelajaran Kooperatif Tipe TAI (Team Assisted Individualization) bagi Peserta Didik Kelas VI Sekolah Dasar - Mariyana, Dian (Universitas Sebelas Maret, 2020)
This research is a classroom action research that aims to determine the improvement of science learning outcomes about the solar system through the application of the TAI (Team Assisted Individualization) type of cooperative learning model for class VI students at SD Negeri Wanoja 02 Wanoja Village, Salem District, Brebes Regency in the second semester of the 2018 academic year. /2019 The subjects of this study were 30 grade VI students, this research was conducted in two cycles, each cycle having an objective test. The results of the research that have been carried out are obtained in the first cycle the percentage of student activity is 6%, the average grade at the time of the post test has only reached 65.8 with students' classical learning mastery of 50%, then in the second cycle the percentage of student activity is 55.56% , the average value increased to 80.28 with students' classical learning completeness of 83%, so it can be concluded that the application of the TAI type cooperative learning model in science lessons about the solar system can improve the learning outcomes of sixth grade students at SD Negeri Wanoja 02, Salem District, Regency Brebes.